Development of Meso‐Substituted Heterocyclic BODIPY‐Based Polymeric Nanoparticles for Pathogen Inhibition using Photodynamic Therapy. Issue 2 (28th October 2022) - Kirar, Seema; Reddy, Yeddula Nikhileshwar; Chand Banerjee, Uttam; Bhaumik, Jayeeta
Abstract: In this work, a series of novel small fluorophores, meso‐substituted heterocyclic BODIPYs were designed and synthesized as phototherapeutic agents. Boron dipyrromethene (BODIPY) dyes are promising chromophores and currently used as a sensitizers in photodynamic therapy (PDT). However, BODIPY as an organic photosensitizer (PS), suffers from poor hydrophilicity resulting in low efficiency in biological applications. To overcome these problems, biopolymer (gelatin) based nanoparticles are developed to incorporate BODIPYs, to achieve phototherapeutic nanoagents (BODIPY‐GNPs) in the aqueous system. More importantly, BODIPY‐GNPs have better in vitro physicochemical properties in the aqueous medium than native BODIPYs. The BODIPY‐GNPs were further explored for their photo‐inhibition activity towards Gram‐positive and Gram‐negative bacteria and fungi using LED as the light source. These BODIPY molecules also showed the ability to intercalate the DNA in vitro. This study provides a new avenue to design therapeutic agents for biomedical applications in photodynamic therapy. Abstract : Nanoencapsulation : Various meso ‐substituted BODIPYs entrapped into gelatin nanoparticles (BDP‐GNPs) enhance the photophysical properties, such as, fluorescence and singlet‐oxygen generation. These nanoagents come in contact with microbes and rupture the cell walls.